Pengelolaan Bengkel Kerja Dalam Mempersiapkan Kemandirian Lulusan Di Smk Satya Karya Karanganyar - Gusbantoro, Hano; , Prof. Dr. Sutama, M.Pd (2015)
The purpose of this study was to describe the management of workshop at Vocational School Satya Karya Karanganyar including planning, procurement, inventory, using, maintenance, and supervision in independence preparing graduates. This type of research is qualitative. The research approach using phenomenology. Subjects were principals, teachers, chairman of expertise program, and chairman of the workshop. Methods of data collection using in-depth interviews, observation and documentation. Data were analyzed using interactive analysis. The results showed that the management of workshop at Vocational School Satya Karya Karanganyar namely: (1) planning is done through a needs analysis and selection of equipment; (2) the procurement is done by buying and receiving assistance; (3) an inventory carried out by the equipment recorded in the book inventory and provide code inventory, (4) the use of workshop has been organized by the head of the workshop so there is no clash between the classes; (5) maintenance of a differentiated by size and the size of the state of the goods; (6) oversight of procurement workshops conducted with sheet monitoring and verification, monitoring inventory process is done every year, Supervision in the maintenance process is done with the control sheet to be filled students and verified by the chairman of the monitoring program was then held. Keyword : management, workshop.